2001
DOI: 10.1177/002234090105500105
|View full text |Cite
|
Sign up to set email alerts
|

The Hamilton SPE Evaluation Tool (HSET): Is it Any Good?

Abstract: Presents the Hamilton Supervised Pastoral Evaluation Tool (HSET). HSET is a self-report that evaluates student learning in a basic SPE unit utilizing six areas: supervisory relationship, personal growth, professional growth, theological reflection, learning context, and overall growth. Reviews statistics involving seven regional units consisting of 18 SPE units with 101 students. Utilizes methodological, investigator, and data triangulation by drawing on qualitative study and CAPPE accreditation review. Discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A more recent study by O'Connor et al (2001) focused on creating and assessing a program evaluation measure of a CPE program-the Hamilton SPE Evaluation Tool (HSET). The study found that CPE students scored highly at the end of the unit on almost all pastoral skills measured.…”
Section: Major Studies Of Cpementioning
confidence: 99%
“…A more recent study by O'Connor et al (2001) focused on creating and assessing a program evaluation measure of a CPE program-the Hamilton SPE Evaluation Tool (HSET). The study found that CPE students scored highly at the end of the unit on almost all pastoral skills measured.…”
Section: Major Studies Of Cpementioning
confidence: 99%
“…Formally articulated in the ACPE Standards, CPE assessment focuses on curricular objectives, student learning outcomes, and individualized contracts for learning as the basis for training and evaluation. Traditionally CPE outcomes are evaluated qualitatively, using the personal testimony or subjective interpretation by CPE supervisors and students (Fitchett & Gray, 1994;O'Conner et al, 2001;Wilson, 2004). Without standard tools or measurements, assessment lacks inter-rater reliability.…”
mentioning
confidence: 99%